Polarising Ushuaia: informal settlements and tourism in an Antarctic gateway city. Issue 11 (1st December 2020) - Herbert, Andrea; Liggett, Daniela; Frame, Bob
ABSTRACT: Ushuaia, one of five Antarctic gateway cities worldwide, is one of the most prosperous places in Argentina. However, its initial impression to visitors as a highly affluent town can be misleading. Since the mid-2000s, informal settlements have sprung up in the forest belt above the city with an estimated 14% of Ushuaia's population. These contrasting representations, polar opposites in some ways, are integral parts of Ushuaia and its positioning as a forward-thinking, culturally differentiated Antarctic gateway city. This paper explores this tension through a case study of two settlements in the northwest of the city, including informal settlers' lived experiences and aspirations; representations and processes of urban development, and the views of the formally tenanted population. Ethnographically exploring a topic that has divided Ushuaia for decades and giving a voice to inhabitants of informal settlements adds depth to an otherwise incomplete and top-down understanding of Ushuaia as a tourist town. Informal settlements are an integral part of the city that could, potentially, add value to tourism enterprises and enrich the tourist gaze by providing a less polarised, more inclusive perspective.